REGIONAL ANESTHESIA CONTINUOUS BRACHIAL PLEXUS BLOCK WITH ULTRASONOGRAPHY GUIDANCE - A., Senapathi T. G.; M., Wiryana; P., Astawa; M., Astawa N.; S., Maliawan; M., Bakta; T., Suryadi N.; M., Sukrama D.; D., Satoto; B., Mahadewa T. G.; Ekaputra, Ekaputra; A., W. (BALI MEDICAL JOURNAL, 2015)
Background: Regional anesthesia has an anti-inflammatory effect that blockade the C-fiber hence reduced cytokine production and blocked the activity of the sympathetic nerve fibers. Postoperative pain caused primarily by tissue inflammation and activity of the C-fibers in the manner of reduced the production of cytokines, regional anesthesia may limit the inflammatory response after surgery and severity of postoperative pain. Methods: This study is a clinical experimental study with randomized pre and post test control group design. A total of 24 samples were recruited in this study divided into two groups each consisting of 12 samples. The first group was given regional anesthesia method of continuous brachial plexus block with ultrasound guidance and the second group with general anesthesia method. T-test or Mann Whitney continued multivariate linear regression analysis was performed to analyze the differences in treatment and not because of differences in the initial values with significance level of p